Accounting for the microstructure in the prediction of the fatigue life of injection moulded composites for automotive applications. (1st January 2021) - Sabiston, Trevor; Li, Bin; Kang, Jidong; Wilkinson, David; Engler-Pinto, Carlos
Abstract: Fatigue characterization of injection moulded carbon fibre is conducted on specimens from ten locations on a flat plaque and two locations from an automotive oil pan. Fatigue testing was carried out using tension–tension and fully reversed loading at room temperature and 120 °C using the specimens from the flat plaques. The stiffness and microstructure of the ten locations are used to calibrate a micromechanics model to evaluate the maximum interface stress for the stresses applied during the fatigue tests. Using the peak interface stress as a failure criteria is proposed and verified by the reduction in variability in the fatigue results. The model is validated on the data set for the two automotive component locations under fully reversed loading at 120 °C.